An evaluation of dendroecological indicators of snow avalanches in the Swiss Alps - Casteller, Alejandro; Stöckli, Veronika; Villalba, Ricardo; Mayer, Andrea C. (Institute of Arctic and Alpine Research, University of Colorado, 2007)
ISSN:15230430